The Effect of Communication Effectiveness and Service Excellence in Achieving Customer Intimacy: Customer Knowledge as Moderating - Lestari, Nimas Dewi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
Customer intimacy is a business strategy that is implemented by giving high attention to the strategy of marketing relationships. In the long term, customer intimacy can positively impact a company. There are several ways to increase customer intimacy. Some of them are through effective communication, service excellence, and customer knowledge. Bank Syariah Indonesia is one of the banks that implement a service excellence strategy for customers, and even Bank Syariah Indonesia has won awards in the field of service excellence. The purpose of this survey is to determine the effect of effective communication and service excellence in increasing customer intimacy through the moderating of variable customer knowledge. This research uses quantitative methods. Sampling in this study used snowball sampling techniques, with a total sample of 100 customers. The results of this study indicate that communication effectiveness and service excellence have a significant effect on increasing customer intimacy, and communication effectiveness has no effect on customer intimacy with variable moderation customer knowledge, and service excellence has a significant positive effect on increasing customer intimacy with moderation variable customer knowledge. This research is expected to provide benefits for various parties in improving the quality of interaction between banks and customers, to create closer and more sustainable relationships, emphasizing the need to implement service excellence to create a positive customer experience and increase loyalty, and optimizing the use of customer knowledge to adjust service and communication strategies to suit customer needs better.